Experimental and numerical investigation of hydrothermal effect on mechanical properties of adhesively bonded T-joint
The moisture environment is a significant problem in designing the adhesive joint in any application. Urea fluidisation bed was washed with hot condense water thus created moisture environmental factor. This situation was cited as a problem in designing adhesively bonded T-joint referring joint part in urea fluidization bed. The purpose of this study was to examine hydrothermal effect on adhesively bonded T- joints with different adhesive thickness in hot water test at temperatures of 80°C, 90°C and 100°C. Two environmental conditions were studied, namely room temperature and dry (RTD) and elevated water temperature (EWT) at 80°C, 90°C and 100°C immersed for 15 minutes. Various bond thickness involved in testing namely 0.5mm, 1.0mm, 1.5mm and 2.0mm. Moreover, the moisture dependence of joint strength was evaluated by comparing those properties with the values at room temperature. Uniaxial loading was performed using a compression test of bulk specimen for both RTD and EWT condition. Another series of tests was run involving T-joint specimen with tensile loading for different adhesive thickness. Finally, the performance of the T-joint application in experiment was compared with the geometrical modelling of T-joint in ANSYS 14.0 software finite element analysis (FEA). Moreover, failure stress was determined as a criteria to investigate the adhesive performance. Results were presented for the best adhesive thickness and moisture environment for Araldite epoxy adhesive. Direct presence of moisture at the adhesive interface alters the interfacial integrity of the adhesive joint. However, the strength of test T-joint specimen immersed in 80°C of hot water and bond thickness 1.5mm appeared to have high strength compared with T-joint specimen at RTD. Moreover, the compressive strength also showed similar behaviour of reductions under the hot water condition. Furthermore, the approach to predict an experimental result using the commercialised finite element software, the ANSYS 14.0 resulted in a good agreement of similar pattern of failure stress curves. The simulation model has been predicted, thus can be used to simulate the T-joint and adhesives at numerous boundary conditions.